Tombiruo Ent.: Multipurpose Food Slicer / Mohd Zaid Khair Mohd Kasim ... [et al.] - Mohd Kasim, Mohd Zaid Khair; Rohata, Muhammad Dinie Hilmi; Abdul Aziz, Muhammad Amreel Luqman; Ahmad Fauzi, Muhammad Fakhrurrazi; Julasri, Nurul Manishah (2019)
Our mission is to invent products that can make other people lives more easier. Our company guarantees that our product is an eco-friendly product as our vision is not only to provide technology to people but also creating technology that could conserve energy. Our product which Multipurpose Food Slicer can ensure that the product can be more helpful for people in a SME, catering and F &B industries.